Genetic Diversity and Structure of Natural, Planted and Selected Populations of Tree Bean (Parkia timoriana (DC.) Merr.) in North East India - Lyngdoh, N; Phurailatpam, C.S.; Jaganathan, Manokar; Thunga, Pavan Kumar; Pownitha, K.V.; Ravikanth, G.; Mehra, T.S. (Indian Forester, 2022)
Planted populations of indigenous fruit trees (IFTs) in the tropics may be the link towards efficient utilization and conservation of its genetic resources, but little is known of the genetic diversity they harbor. Tree bean (Parkia timoriana) is an economically important IFT that is cultivated and planted on and off farm in tropical regions of Northeast India. Using 3-microsatellite markers, we compared the genetic variation and structure of five-planted populations and a farmer-selected with three natural populations within northeast India. Pooled planted and selected populations showed marginal reduction in genetic diversity values compared to natural populations. Individually, cultivated populations from Manipur had higher Shannon diversity index (I=1.30 and 1.32) compared to wild populations (I= 1.30, 1.08 and 1.12). The farmer selected population displayed appreciable levels of diversity (Na= 5.33 and I=1.12). Structure analysis revealed high degree of admixture in natural and two planted populations and PCA depicted close congruence with the geographical distribution of populations. The present study reveals that famer driven selection process has not resulted to any major reduction in genetic diversity. There is ample diversity with natural as well as planted populations of the species, which shall be crucial components for trait improvement in tree breeding programs.